REPRESENTASI NILAI-NILAI AKHLAK DALAM FILM NUSSA: Media Alternatif Untuk Pembelajaran Akidah Akhlak Di MI - Nurfaizah, Nabila Yumna (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the representation of moral values in the animated film Nussa as an alternative medium for teaching Akidah Akhlak in Madrasah Ibtidaiyah (MI), particularly in second grade. The study focuses on moral categories based on their objects, namely morality toward Allah SWT, toward fellow human beings, and toward the environment. This research employs a qualitative approach using library research and content analysis techniques based on Krippendorff's model. Primary data were obtained from twelve episodes of the Nussa film, analyzed based on narrative, dialogue, and visual context; while secondary data included textbooks, scientific journals, and curriculum documents. The analysis results indicate that the Nussa film consistently represents moral values aligned with the core competencies of Akidah Akhlak for second-grade MI students. Akhlak towards Allah is depicted through the practice of prayer, gratitude, and reverence for His creation; akhlak towards others is shown through the values of honesty, empathy, and politeness; while akhlak towards the environment is evident through the strengthening of children's ecological awareness. This film is not merely entertaining but also serves as a contextual, enjoyable, and effective educational tool in supporting the internalization of Islamic moral values among young students. ABSTRAK Penelitian ini bertujuan untuk menganalisis representasi nilai-nilai akhlak dalam film animasi Nussa sebagai media alternatif dalam pembelajaran Akidah Akhlak di Madrasah Ibtidaiyah (MI), khususnya kelas II. Kajian difokuskan pada kategori akhlak berdasarkan objek, yaitu akhlak kepada Allah Swt., kepada sesama manusia, dan kepada lingkungan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi pustaka (library research) dan teknik analisis isi berdasarkan model Krippendorff. Data primer diperoleh dari dua belas episode film Nussa yang dianalisis berdasarkan narasi, dialog, dan konteks visual; sedangkan data sekunder mencakup buku teks, jurnal ilmiah, dan dokumen kurikulum. Hasil analisis menunjukkan bahwa film Nussa secara konsisten merepresentasikan nilai-nilai akhlak yang selaras dengan kompetensi dasar Akidah Akhlak kelas II MI. Akhlak kepada Allah digambarkan melalui praktik berdoa, rasa syukur, dan pengagungan terhadap ciptaan-Nya; akhlak kepada sesama ditampilkan melalui nilai jujur, empati, dan sopan santun; sedangkan akhlak kepada lingkungan tampak melalui penguatan kesadaran ekologis anak. Film ini tidak hanya bersifat hiburan, tetapi juga berfungsi sebagai sarana edukatif yang kontekstual, menyenangkan, dan efektif dalam mendukung proses internalisasi nilai-nilai moral Islam pada siswa usia dini.